Counsellor Trainee Awareness of Evaluative Criteria: A Neglected Variable - Toukmanian, Shaké G.; Capelle, Ronald G.; Rennie, David L. (Canadian Journal of Counselling and Psychotherapy, 2012)
The counselling performances of undergraduates given 9 weeks of systematic training in either human relations training or microcounselling and of subjects receiving, prior to posttest, brief specific instructions on how to counsel, were compared to the performance of a no-training control group. Fifty-five undergraduate volunteers acted as clients. Empathy and three categories of microcounselling behaviour counts served as criteria. Positive and significant training effects were found. There were no significant differences between the training group and the group receiving specific instructions. The findings were interpreted to indicate that controlling the trainee knowledge of the criteria of evaluation is essential in research assessing the effectiveness of counsellor training programmes.